Dynamic effects of fiscal and monetary policy instruments on environmental pollution in ASEAN (2021)
This study aims to re-examine the impacts of monetary and fiscal policy on environmental quality in ASEAN countries from 1990 to 2019. We utilized the panel and time series NARDL approach to explore the long-run and short-run estimates at a regional level and country level. ASEAN regional-wise analysis shows that contractionary monetary policy reduces the CO2 emissions, while expansionary monetary policy enhances CO2 emissions in the long run. The long-run coefficient further confirms that expansionary fiscal policy mitigates CO2 emissions in ASEAN. The impact of expansionary monetary and fiscal policy on CO2 emissions is positive and significant, while contractionary monetary and fiscal policy have an insignificant impact on CO2 emissions in the short run. ASEAN country-wise analysis also reported the country-specific estimates for the short and long run. Some policies can redesign in light of these novel findings in ASEAN economies.